Study on Disinfestation of Fruit Fly (Bactrocera dorsalis) Using Vapor Heat Treatment on Gedong Gincu Mango - Rokhani Hasbullah; Dadang .; Elpodesy Marlisa (Jurnal Keteknikan Pertanian, 2009)
Since the prohibition of chemical method for insect disinfestations processes such as ethylene dibromide in 1984, heat treatment method was developed as quarantine technology. One of the heat treatment methods is vapor heat treatment (VHT). The objectives of this research were to study mortality of fruit fly (Bactrocera dorsalis) and to study the responses of VHT on quality of gedong gincu mango. Fruit fly mortality due to heat has been investigated by immersing fruit fly eggs into heated water at temperatures of 40, 43, 46 and 49OC for 30 minutes immersed, also at temperature of 46OC for 5, 10, 15, 20, 25 and 30 minutes. Gedong gincu mangoes were treated at temperature 46.5OC for 0, 10, 20, and 30 minutes. The results showed that mortality has been achieved 100% at temperature more than and equal to 43OC for 30 minutes and attemperature 46OC for more than and equal to 10 minutes. The VHT has significantly and fungi population although without adversely affecting to the fruit quality and there were no significant change in the fruit weight loss, hardness, color, soluble solid content, water content, vitamin C and organoleptic test. VHT at temperature 46.5OC for 20 up to 30 minutes were effective to kill fruit flies inside mangoes and were able tomaintaining mango quality during storage.Keywords : mango, fruit fly, disinfestations, vapor heat treatmentDiterima: 24 Maret 2008; Disetujui: 22 Oktober 2008